Slagging agent and preparation method thereof
By recycling and slag-based agent prepared by vanadium-extracting corundum slag, limestone, industrial soda ash and clay, the shortcomings of active limes and fluorite during ladle refining are solved, and the slag-based effect is improved and the production cost is reduced, while reducing environmental pollution.
Patent Information
- Application Number
- CN202411776618.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
During the refining process of existing ladles, the use of active lime leads to hard slag shells and poor fluidity of slag surfaces, which reduces the desulfurization efficiency and extends the refining time. In addition, fluorite has problems of instability and environmental pollution as a slag agent, and mineral resources are increasingly scarce.
By recycling corundum slag produced by vanadium extraction, combining limestone, industrial soda ash and clay, a slag agent is prepared. The slag agent reacts with white ash in the slag surface under electric heating to generate low-melting substances and decompose to produce CO2 gas, improving the slag effect, and reducing the melting point of the slag through industrial soda ash.
The slag-chemical effect has been improved, and the production cost has been reduced. The slag-chemical agent does not contain fluorine, reducing the environmental pressure of steel mills.
Smart Images

Figure BDA0005171637740000021 
Figure BDA0005171637740000031 
Figure BDA0005171637740000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ladle refining, in particular to a slagging agent and a preparation method thereof. Background Art
[0002] The LF refining process uses relatively cheap active lime for desulfurization, which is one of the measures for steel mills to reduce costs. However, due to the high melting point of active lime, the large-scale use of active lime will result in a harder slag shell and poor slag surface fluidity, which will not only greatly reduce the desulfurization efficiency of active lime, but also extend the refining time, lead to low subsequent refined alloy yield, low heating efficiency, and increased electrode consumption.
[0003] Fluorite is often used for slag removal in steelmaking, but in actual use, the slag removal effect is often unstable, and fluorite is an important factor in the erosion of furnace linings and ladle linings. At the same time, a large amount of F- ions are generated during use, which causes great pollution to the ecological environment. With the country's restrictions on the exploitation of mineral resources, the price of fluorite is also increasing. Therefore, steel companies are looking for a low-cost refining slag removal agent that can replace fluorite. Fluorine-free steelmaking has become the development trend of today's molten steel refining. At present, calcium aluminate, low-grade bauxite, cryolite and other resources are generally used to produce Al2O3-based slag removal agents, but these mineral resources are becoming increasingly scarce and their prices are also rising.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a slag-forming agent and a preparation method thereof. The slag-forming agent can recycle the corundum slag produced by vanadium extraction, has good slag-forming effect, low production cost, and does not contain fluorine, so it is more environmentally friendly.
[0006] The first aspect of the present invention provides a slagging agent, the raw materials of which include the following components: corundum slag, limestone, industrial soda ash and clay.
[0007] Preferably, the particle size of the corundum slag is 0-3 mm, the particle size of the limestone is 1-3 mm, the particle size of the industrial soda ash is 0.074-1 mm, and the particle size of the clay is 0.074-1 mm.
[0008] Preferably, the composition comprises, by weight: 65 to 80 parts of corundum slag, 10 to 20 parts of limestone, 5 to 15 parts of industrial soda ash and 3 to 6 parts of clay.
[0009] Preferably, the corundum slag comprises, by mass percentage, 52-60% Al2O3, 10-15% CaO and 10-15% MgO.
[0010] Preferably, in terms of mass percentage, the CaCO3 content in the limestone is greater than or equal to 90%, the H2O content in the limestone is less than or equal to 1%, and the loss on ignition of the limestone is greater than or equal to 25%.
[0011] Preferably, the Na2CO3 content in the industrial soda ash is greater than or equal to 99% by mass.
[0012] Preferably, in terms of mass percentage, the SiO2 content in the clay is 40-55%, and the H2O content in the clay is less than or equal to 3%.
[0013] The second aspect of the present invention provides a method for preparing a slag-forming agent, comprising mixing and stirring various raw materials evenly, and then pressing them into pellets to obtain the slag-forming agent.
[0014] Preferably, the slag-forming agent is an ellipsoid (preferably 30 mm×30 mm), the pellet strength is greater than 800 N, and the powder surface ratio less than or equal to 5 mm is no more than 5%.
[0015] Preferably, ton bags with inner film bags are used for packaging, which has better moisture-proof effect.
[0016] Preferably, the slagging agent meets the following physical and chemical indicators (as shown in Table 1).
[0017] Table 1
[0018]
[0019]
[0020] A third aspect of the present invention provides a method for using a slag-forming agent, wherein the slag-forming agent is added when lime is added during the steelmaking process, and the slag-forming agent is used under electric heating.
[0021] The present invention has at least the following beneficial effects:
[0022] The present invention recycles Al2O3 and CaO in vanadium corundum slag and combines them with lime to generate low melting point substances such as seven aluminums and twelve calciums, and then adds limestone and industrial soda ash, and utilizes the characteristics of the two substances being decomposed by heat to decompose and generate CO2 gas on the slag surface, thereby promoting a slag-forming agent to better react with the lime on the slag surface. At the same time, Na2O generated by the decomposition of industrial soda ash is utilized to reduce the melting point of the slag. The slag-forming agent of the present invention has good slag-forming effect and low production cost, and the slag-forming agent does not contain fluorine, thereby greatly reducing the environmental pressure of the steel plant. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The present embodiment provides a slagging agent, the raw materials of which include the following components: 70 parts by weight of corundum slag with a particle size of 0-3 mm, 15 parts by weight of limestone particles with a particle size of 1-3 mm, 10 parts by weight of industrial soda ash with a particle size of 0.074 mm-1 mm, and 5 parts by weight of clay particles with a particle size of 0.074 mm-1 mm.
[0028] Corundum slag contains 52-60% Al2O3, 10-15% CaO and 10-15% MgO.
[0029] The CaCO3 in limestone is ≥90%, the loss on ignition is ≥25%, and the H2O is ≤1%.
[0030] Na2CO3 in industrial soda ash ≥99%.
[0031] The SiO2 in clay is 40% to 55%, and H2O ≤ 3%.
[0032] The present embodiment also provides a method for preparing a slagging agent, comprising the following steps: feeding the above-mentioned raw materials that have passed the inspection into a planetary mixer for mixing and stirring, after mixing and stirring for 1 minute, adding 5% water and continuing to stir for 3 minutes, putting the mixed material into a ball press through a belt, and the pressed balls are dried for 3 days and then packaged at 500 kg / bag after passing the inspection, and are fastened with opening labels and put into storage for use.
[0033] The samples were taken to test the physical and chemical indicators of the slag-making agent of this embodiment (the test results are shown in Table 2), and the samples were transported to a steel plant after passing the test.
[0034] Table 2
[0035] project Test results% <![CDATA[Al2O3,wt%]]> 42.14 CaO, wt% 12.73 MgO,wt% 7.11 <![CDATA[Na2O]]> 6.78 Pellet strength, N 1324 ≤5mm powder surface rate, % 1.34
[0036] The slag-removing agent of the present embodiment was sent to a steel plant. The steel grade produced was Q235B. It was added during electric heating. The addition amount for each furnace of molten steel was 220 tons and 300 kg was added. A total of 5 furnaces were produced, and the amount of slag-removing agent used was 1.5 tons. The use effect is shown in Table 3. It can be seen from Table 3 that the slag-removing agent of the present embodiment has a good slag-removing effect.
[0037] Table 3
[0038] serial number Electric heating time, min Amount of lime used, t Slag surface melting effect 1 12.5 1.2 All melted 2 12 1.3 All melted 3 13 1.2 All melted 4 13 1.1 All melted 5 10 1.2 All melted
[0039] Example 2
[0040] The present embodiment provides a slagging agent, the raw materials of which include the following components: 78 parts by weight of corundum slag with a particle size of 0-3 mm, 10 parts by weight of limestone particles with a particle size of 1-3 mm, 8 parts by weight of industrial soda ash with a particle size of 0.074 mm-1 mm, and 4 parts by weight of clay particles with a particle size of 0.074 mm-1 mm.
[0041] Corundum slag contains 52-60% Al2O3, 10-15% CaO and 10-15% MgO.
[0042] The CaCO3 in limestone is ≥90%, the loss on ignition is ≥25%, and the H2O is ≤1%.
[0043] Na2CO3 in industrial soda ash ≥99%.
[0044] The SiO2 in clay is 40% to 55%, and H2O ≤ 3%.
[0045] The present embodiment also provides a method for preparing a slagging agent, comprising the following steps: feeding the above-mentioned raw materials that have passed the inspection into a planetary mixer for mixing and stirring, after mixing and stirring for 1 minute, adding 5% water and continuing to stir for 3 minutes, putting the mixed material into a ball press through a belt, and the pressed balls are dried for 3 days and then packaged at 500 kg / bag after passing the inspection, and are fastened with opening labels and put into storage for use.
[0046] Sampling was conducted to test the physical and chemical indicators of the slag-removing agent (the test results are shown in Table 4), and the slag-removing agent was transported to a steel plant after passing the test.
[0047] Table 4
[0048]
[0049]
[0050] The slag-removing agent of the present embodiment was sent to a steel plant. The steel grade produced was Q355B. It was added during electric heating. The addition amount for each furnace of molten steel was 220 tons and 300 kg was added. A total of 4 furnaces were produced. The amount of slag-removing agent used was 1.2 tons. The use effect is shown in Table 5. It can be seen from Table 5 that the slag-removing agent of the present embodiment has a good slag-removing effect.
[0051] Table 5
[0052] serial number Electric heating time, min Amount of lime used, t Slag surface melting effect 1 14 1.5 All melted 2 13 1.3 All melted 3 12 1.2 All melted 4 13 1.2 All melted
[0053] According to the background technology of the present invention and the contents of Examples 1 and 2, it can be concluded that the slag-removing agent of the present invention has a good effect on slag-removing in electric heating, which has a favorable impact on energy conservation and emission reduction, cost reduction and environmental protection pressure in steel plants, and has broad application prospects.
[0054] Comparative Example 1
[0055] This comparative example is basically the same as Example 1, except that the corundum slag is removed from the raw materials of this comparative example.
[0056] After testing, it was found that the electric heating time needed to be extended to 16 minutes when the slag-removing agent in this comparative example was used, and the melting effect was significantly weakened.
[0057] Comparative Example 2
[0058] This comparative example is basically the same as Example 1, except that limestone is removed from the raw materials of this comparative example.
[0059] After testing, it was found that the electric heating time of the slag-removing agent in this comparative example was consistent when used, but white ash still clumped around the slag surface of the ladle tank.
[0060] Comparative Example 3
[0061] This comparative example is basically the same as Example 1, except that industrial soda ash is removed from the raw materials of this comparative example.
[0062] After testing, it was found that the electric heating time was still prolonged when the slag-melting agent in this comparative example was used, which was required to be 15 minutes, and the slag surface was not completely melted.
[0063] Comparative Example 4
[0064] This comparative example is basically the same as Example 1, except that limestone and industrial soda ash are removed from the raw materials of this comparative example.
[0065] After testing, it was found that when the slag-removing agent of this comparative example was used, except for the melting range where the slag-removing agent was added, the rest of the slag surface had the phenomenon of white ash clumping.
[0066] Comparative Example 5
[0067] This comparative example is basically the same as Example 1, except that clay is removed from the raw materials in this comparative example.
[0068] After testing, it was found that the slag-forming agent in this comparative example had a high powder rate during the production process, and the initial ball-forming rate dropped seriously, which had a huge impact on the production cost. In addition, it produced a lot of smoke and dust during use, and the use effect was poor.
[0069] Comparative Example 6
[0070] This comparative example is basically the same as Example 1, except that: in this comparative example, the particle size of the corundum slag is 1-3 mm, the particle size of the limestone is 1-3 mm, the particle size of the industrial soda ash is 0.074 mm-1 mm, and the particle size of the clay is 0.074 mm-1 mm.
[0071] After testing, it was found that the slag-reducing agent in this comparative example had too much aggregate, resulting in a powder rate of 3.42%, and a small amount of dust was generated during use.
[0072] Comparative Example 7
[0073] This comparative example is basically the same as Example 1, except that: in this comparative example, the particle size of the corundum slag is 0-1 mm, the particle size of the limestone is 0-1 mm, the particle size of the industrial soda ash is 0.074 mm-1 mm, and the particle size of the clay is 0.074 mm-1 mm.
[0074] After testing, it was found that the slagging agent in this comparative example had too little aggregate, resulting in a decrease in the later strength of the pellets, which was only 867N. A small amount of pellets were broken during bagging, shipment, and entering the silo.
[0075] In summary, the present invention recycles Al2O3 and CaO in the vanadium corundum slag and combines them with lime to generate low-melting-point substances such as seven aluminums and twelve calciums, and then adds limestone and industrial soda ash, and utilizes the characteristics of the two being decomposed by heat to decompose and generate CO2 gas on the slag surface, thereby promoting the slag-forming agent to better react with the lime on the slag surface. At the same time, Na2O generated by the decomposition of industrial soda ash is utilized to reduce the melting point of the slag. The slag-forming agent of the present invention has good slag-forming effect and low production cost, and the slag-forming agent does not contain fluorine, which greatly reduces the environmental protection pressure of the steel plant.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A slagging agent, characterized in that: The raw materials include the following components: corundum slag, limestone, industrial soda ash and clay.
2. The slag-removing agent according to claim 1, characterized in that: The particle size of the corundum slag is 0-3 mm, the particle size of the limestone is 1-3 mm, the particle size of the industrial soda ash is 0.074-1 mm, and the particle size of the clay is 0.074-1 mm.
3. The slag-removing agent according to claim 1, characterized in that: Calculated by weight, it comprises: 65-80 parts of corundum slag, 10-20 parts of limestone, 5-15 parts of industrial soda ash and 3-6 parts of clay.
4. The slag-removing agent according to claim 1, characterized in that: Calculated by mass percentage, the corundum slag includes: 52-60% Al2O3, 10-15% CaO and 10-15% MgO.
5. The slag-removing agent according to claim 1, characterized in that: Measured by mass percentage, the CaCO3 content in the limestone is greater than or equal to 90%, the H2O content in the limestone is less than or equal to 1%, and the loss on ignition of the limestone is greater than or equal to 25%.
6. The slag-removing agent according to claim 1, characterized in that: Calculated by mass percentage, the Na2CO3 content in the industrial soda ash is greater than or equal to 99%.
7. The slag-removing agent according to claim 1, characterized in that: Calculated by mass percentage, the SiO2 content in the clay is 40-55%, and the H2O content in the clay is less than or equal to 3%.
8. The method for preparing the slag-removing agent according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing and stirring various raw materials evenly, and then pressing them into pellets to obtain the slag-forming agent.
9. The method for preparing the slag-removing agent according to claim 8, characterized in that: The slag-forming agent is an ellipsoid, the pellet strength is greater than 800N, and the powder surface ratio less than or equal to 5mm is not more than 5%.
10. The method for using the slagging agent according to any one of claims 1 to 7, characterized in that: The slag-removing agent is added when lime is added in the steel-making process, and the slag-removing agent is used under electric heating.